CONSEQUENCES OF FINANCIAL CRISIS ON LOAN PROVIDING FUNDS FOR SMALL & MEDIUM ENTERPRISES FORMER PREFECTURE OF SERRES -GREECE - Chrysanthi Balomenou; Marianthi Maliari (European Regional Science Association (ERSA), 2011)
It is common knowledge that Small and Medium enterprises make up the backbone of the Greek economy. Nowadays during the greatest post war financial crisis, the fund availability critically determines the survival and the development of almost every enterprise. In the first part of this presentation we will refer to the financial crisis in Greece. Apparently one of the major economic problems in our country is the widely extended corruption throughout all the economic activities including corruption 0n banks. In the second part we will present the impact of the recession on the banking sector in local and national level and the consequences of the great reduction of loan providing funds to Small and Medium Enterprises (SMEs). We will present the fact that nowadays, entrepreneurs can not obtain loans based on personal guarantee, and they have to offer their own house as collateral. In the third part we will refer to Serres, former prefecture of Greece, where the economic inability and underdevelopment to all the levels of local economy is obvious. We will also refer to the fact that while on turmoil governments schedule programs using the criterion of efficiency instead of the criterion of equity. Under these circumstances, the area of Serres will never be developed. In the forth part we will present the results of the questionnaire-based research from the local entrepreneurs in the Prefecture of Serres. We will focus on the consequences of a economical crisis. It is worth referring to the fact that their answers are similar to those deduced from the results of the researches that have been referred to in bibliography. Finally we will end this presentation with the main conclusions.
Keywords: 330; Financial crisis; Loan providing funds; Local entrepreneurship; Former Prefecture of Serres